The Legal Protection on Reporters for Corruption Crime - Lusia Sulastri (Jurnal Daulat Hukum, 2022)
Nurhayati's report through a letter to the Head of BPD Citemu, became the turning point for the uncovering of the village fund corruption case that was detrimental to the state. It turned out that the person who had uncovered the village fund corruption case was also named a suspect. Based on this, the authors are interested in studying how legal protection for whistleblowers on corruption crimes is associated with the determination of Nurhayati's suspect status for corruption in Cirebon Regency. This research used literature study with the doctrinal approach. In addition, this study also examines the ideal legal protection for whistleblowers for corruption. The results of the study show that legal protection for whistleblowers for criminal acts of corruption is not running well, as evidenced by the determination of the status of the suspect Nurhayati for Corruption Crimes in Cirebon Regency. This happens because there is no common perception of the position of the Whistleblower on Corruption Crimes as a subject protected by law between the police and the Prosecutor's Office. The ideal legal protection for whistleblowers for criminal acts of corruption is to build legal protection for whistleblowers that is integrated and obeyed by law enforcement officers. The provision of witness protection must of course start from law enforcement who is the spearhead of law enforcement, namely the police.